2000
DOI: 10.2337/diabetes.49.9.1517
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of the peroxisomal proliferator response element in rat GLUT2 promoter.

Abstract: We identified the peroxisomal proliferator response element (PPRE) in the +68/+89 region of the rat GLUT2 gene. To identify whether the putative PPRE in the GLUT2 gene (GLUT2-PPRE) is functional, GLUT2 promoter-luciferase reporter constructs were transfected into CV-1 cells. Promoter activities were increased by coexpression of peroxisomal proliferator-activated receptor (PPAR)-␥, retinoid X receptor (RXR)-␣, and treatment of their ligands; troglitazone and 9-cis retinoic acid potentiated the transactivational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 37 publications
5
86
1
1
Order By: Relevance
“…-196 -184 et al, 2001). On the other hand, PPAR-γ stimulated the promoter activity of genes responsible for glucose sensing apparatus of pancreatic β -cells, suggesting that this ligand could also improve glucosestimulated insulin secretion (Kim et al, 2000;2002b). In the hyperglycemic states of type 2 diabetes, administration of TZDs causes amelioration of blood glucose level, suggesting that the liver glucose sensor can be a direct target of TZDs action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…-196 -184 et al, 2001). On the other hand, PPAR-γ stimulated the promoter activity of genes responsible for glucose sensing apparatus of pancreatic β -cells, suggesting that this ligand could also improve glucosestimulated insulin secretion (Kim et al, 2000;2002b). In the hyperglycemic states of type 2 diabetes, administration of TZDs causes amelioration of blood glucose level, suggesting that the liver glucose sensor can be a direct target of TZDs action.…”
Section: Discussionmentioning
confidence: 99%
“…The labeled probe (10,000 cpm) was incubated with 5 µg of nuclear extract from rat liver for 30 min on ice. The binding reactions were same as described (Kim et al, 2000). To perform supershift assay, the binding mixtures were incubated for 10 min at room temperature in the presence of 1 µ l of anti-PPARγ (Kim et al, 2002a).…”
Section: Electrophoretic M Obility Shift Assay (Em Sa )mentioning
confidence: 99%
See 1 more Smart Citation
“…As such, this mouse showed a phenotype of functional ␤-cell failure, with an expression profile that agreed exactly with the proposed signaling pathway in this study. Also, others have reported PPAR␥ regulation of gene expression for GLUT2 (53), glucokinase (54), and GPR40 (55) in ␤-cells, plus key modulatory effects of PPAR␥ in ␤-cell endoplasmic reticulum stress related to a cytokine-induced loss of SERCA2 expression have been shown (56,57). In addition, numerous ␤-cell effects have been attributed to PPAR␥ from thiazolidinedione studies in islets, insulin-containing cell lines, and various animal models, although direct proof that the findings are PPAR␥-mediated is mostly lacking.…”
Section: Foxo1 and Ppar␥ Signaling In ␤-Cellsmentioning
confidence: 99%
“…PPAR-γ is known to be expressed in the pancreatic islet [7,8], and PPAR-responsive elements have been identified in the promoters of genes involved in glucosestimulated insulin secretion, including Glut2, Gck, IJASR|VOL 01|ISSUE 02|2015 www.ssjournals.com and Pdx1. [9][10][11][12][13] Information from studies of β-cell lines, humans at risk for type 2 diabetes propose that PPAR-γ agonist function and management guides to protection of β-islet cell mass and rodent models of progressive type 2 diabetes [14][15][16][17]. Whereas the studies noted above suggested a direct or indirect effect of PPAR-γ agonists on the biology of the β-islet, no studies to date have observed the molecular or epigenetic mechanisms whereby β-islet cell function is preserved or enhanced in response to PPAR-γ activation.…”
Section: Introductionmentioning
confidence: 99%